THE GENERAL EDUCATION SCIENCE PROGRAM AT WESTERN MICHIGAN COLLEGE. - Van Deventer, W. C.; Kruglak, Haym; Berry, W. J. (Science Education, 1956)
The article focuses on the general education science program offered by the Western Michigan University in Kalamazoo, Michigan. According to the author, this general education program is a flexible program within a rigid general education science requirement. The program offered a total of forty-two hours of general education courses including eight hours of general education science, eight hours of social science, six hours of humanities, six or eight hours of communication skills, four hours of physical education and eight or ten hours elected from a group of courses chosen by the Basic Studies Council, a faculty group that advises the general education program director.